2022
DOI: 10.3390/polym14194224
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, Mechanical, and Morphological Characterisations of Graphene Nanoplatelet/Graphene Oxide/High-Hard-Segment Polyurethane Nanocomposite: A Comparative Study

Abstract: The current work investigates the effect of the addition of graphene nanoplatelets (GNPs) and graphene oxide (GO) to high hard-segment polyurethane (75% HS) on its thermal, morphological, and mechanical properties. Polyurethane (PU) and its nanocomposites were prepared with different ratios of GNP and GO (0.25, 0.5, and 0.75 wt. %). A thermal stability analysis demonstrated an enhancement in the thermal stability of PU with GNP and GO incorporated compared to pure PU. Differential Scanning Calorimetry (DSC) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 91 publications
3
12
0
Order By: Relevance
“…The fact that GO has a high aspect ratio causes it to aggregate to higher concentrations, which increases the number of stress concentration sites and therefore decreases the stress transfer efficiency, which decreases the quality of the resulting composites. [ 48 ] GO is an excellent particle to improve the mechanical properties of a polymer matrix due to its extremely high surface area and high intrinsic mechanical characteristics. [ 49 ] This is due to PVDF‐HFP/PZT composite having excellent dispersion as shown in the SEM data (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The fact that GO has a high aspect ratio causes it to aggregate to higher concentrations, which increases the number of stress concentration sites and therefore decreases the stress transfer efficiency, which decreases the quality of the resulting composites. [ 48 ] GO is an excellent particle to improve the mechanical properties of a polymer matrix due to its extremely high surface area and high intrinsic mechanical characteristics. [ 49 ] This is due to PVDF‐HFP/PZT composite having excellent dispersion as shown in the SEM data (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the surface modification of nanoparticles has become a prominent research topic in materials science. 6 Graphene nanoplates (GNP), commonly referred to as multilayer or exfoliated graphene plates, 7 comprise multiple graphene layers and exhibit properties similar to those of single-layer graphene, despite being relatively easier to produce. Owing to their decent thermal conductivity, GNP are extensively used as fillers to enhance the thermodynamic properties of polyurethane (PU).…”
Section: Introductionmentioning
confidence: 99%
“…However, van der Waals interactions between the GNP and polymer matrix intensify with increasing GNP content, resulting in severe stacking and agglomeration of the GNP, which in turn degrades the properties of the GNP/polymer composites. 7 Surface modification of GNP is the most effective method for preventing GNP agglomeration and increasing the interfacial compatibility between GNP and the PU matrix. 8 The techniques used for modifying the GNP surface mainly include chemical functionalization (covalent bonding) and physical modification (noncovalent bonding; that is, π/π-interaction-based bonding), with the former being more effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Albozahid, M. et al (2022) also investigated the influence of graphene-based nanofiller on PU via in situ polymerization and they concluded that the addition of GNP and GO lead to microphase separation and dramatic increase of the tensile properties of the nanocomposite obtained. 32 On the other hand, Panahi-Sarmad, M. et al (2019) 33 and (2020) 34 developed TPU/graphene nanoparticles SMPCs using GO and reduced graphene oxide (rGO) as fillers and investigated their influence on TPU morphology. From these studies, the authors assumed that GO and rGO nanoparticles have great interaction with the hard and SSs of TPU, respectively.…”
Section: Introductionmentioning
confidence: 99%